Measurement of the lifetime of b-baryons - Abreu, P; Adam, W; Adye, T; Adzic, P; Albrecht, Z; Alderweireld, T; Alekseev, G; Alemany, R; Allmendinger, T; Allport, P; Almehed, S; Amaldi, U; et al. (1999)
The average lifetime of weakly decaying b-baryons was studied using 3.6 million Z0 hadronic decays collected by the DELPHI detector at LEP. The measurement of the proper decay time distribution of secondary vertices was used on three complementary samples. The first sample consisted of events with a fully reconstructed Λ+c and an opposite charge lepton, or an oppositely charged lepton pair accompanied by a Λ0. The other two samples were more inclusive, where b-baryon semileptonic decays were recognized by the presence of either a proton identified by the RICH detector or a Λ0 and a lepton of charge opposite to that of the proton. The combined result was: τ(b-baryon) = 1.14 ± 0.08 (stat) ± 0.04 (syst) ps.